Telomere length as a biomarker for cumulative experience in broiler chickens - Andrew M. Campbell; Mallory G. Anderson; Mark F. Haussmann; Raquel Rowell; Leonie Jacobs (PLoS ONE, 2025)
Cumulative experience can be defined as the sum of all positive and negative experiences during an animal’s lifetime. Telomere length shows promise as a biomarker of cumulative experience in humans and non-human animals but is not yet assessed for broiler chickens. Therefore, our objective was to determine telomere length changes due to positive and negative experiences in fast-growing broiler chickens. In three replicated experiments, male Ross 708 broilers were housed in a 2 × 2 factorial study investigating high environmental complexity as a positive environment (vs. low complexity; 6 pens/treatment) and high stocking density as a negative environment (vs. low density; 6 pens/treatment). Telomere length was quantified at day 48 of age via quantitative RT-PCR (qRT-PCR) from gonad and kidney samples (N = 9 samples/treatment/tissue/experiment). Prior to analysis, raw relative telomere length (rTL) values were z-transformed to allow comparison between experiments. Combined data from the three experiments were analyzed using mixed models with complexity, density, and their interactions as fixed factor and pen nested within experiment and qRT-PCR plate number as random factors. Over all three trials, birds housed in high complexity environments tended (P = 0.0503) to have longer telomeres from kidney tissue than birds housed in low complexity environments. Stocking density did not impact combined kidney telomere length and gonadal telomere length was not impacted by environmental complexity or stocking density. Longer telomeres (statistical trend) in response to positive experience (environmental complexity) when compared to low-complexity indicate that high-complexity environments elicited positive cumulative experience in broiler chickens, although effect size was small. Telomere length has the potential to be a valuable tool in the assessment of cumulative experience in production settings, and future works should replicate these findings and expand upon this work by comparing telomere length with other more traditional animal welfare markers.